(untitled) (Research, Society and Development, 2025)
Objective: To analyze the trend of hospital admissions for surgical procedures and surgical mortality in Brazil from 2010 to 2019. Method: A coefficient of surgical procedures was established for each region of the country, based on data obtained from the Department of Informatics of the Brazilian Unified Health System (DATASUS), through the TABNET platform, focusing on Health Care and Hospital Production. Results: During the study period, 44,306,321 surgical procedures were performed in the public health sector, corresponding to an average of 4,430,632 surgeries per year. The following rates were observed: 2.70 surgeries per 100 inhabitants/year in the South; 2.17 in the Midwest; 2.11 in the Southeast; 2.08 in the Northeast; and 1.93 in the North. The national surgical mortality rate was 1.64%, with regional variations: the highest in the South (2%), followed by the Southeast (1.8%), Midwest (1.50%), Northeast (1.33%), and the lowest in the North (1.15%). Regarding mortality trends, the Northeast and South showed variable patterns, similar to the overall situation in Brazil. Conclusion: Brazil presents a surgical volume below the international target, suggesting that the country falls short of the fundamental rights guaranteed by the Unified Health System.